Analisis Manfaat Penggunaan Sistem Informasi Inlislite Versi 3.0 Di Perpustakaan Umum Daerah Provinsi Dki Jakarta Dengan Metode PIECES - Afdha, Suchia; Ardoni, Ardoni (Departemen Informasi Perpustakaan dan Kearasipan, 2023)
This study was aimed to describe the benefits of using the INLISLite information system version 3.0 at the DKI Jakarta Provincial Public Library using the PIECES method. This research is a quantitative research with a descriptive approach. The sample was conducted by random sampling method. Collecting data was conducted by distributing questionnaires to respondents via google form, namely Librarian of DKI Jakarta Provincial Public Library. The statistical method used editing and tabulation. The validity test uses the Pearson product moment formula and the reliability test uses the Cronbach alpha formula. The result of this research showed that the use of the INLISLite information system version 3.0 at the DKI Jakarta Provincial Public Library provides benefits in terms of performance, information, economy, control, efficiency and service, depite there are some efficiency aspects that don’t work.